Essentials of computing systems - Fernandes, João M. (2022)
Computers were invented to "compute", i.e., to solve all sort of mathematical problems. A computer system contains hardware and systems software that work together to run software applications. The underlying concepts that support the construction of a computer are relatively stable. In fact, (almost) all computer systems have a similar organization, i.e., their hardware and software components are arranged in hierarchical layers (or levels) and perform similar functions. This book is written for programmers and software engineers who want to understand how the components of a computer work and how they affect the correctness and performance of their programs.